Money and finance after the crisis critical thinking for uncertain times - Christophers, Brett 1971; Leyshon, Andrew; Mann, Geoff (Antipode book series., 2017)
"Money and Finance After the Crisis provides a critical multi-disciplinary perspective on the post-crisis financial world in all its complexity, dynamism and unpredictability. Contributions illuminate the diversity of ways in which money and finance continue to shape global political economy and society."--Provided by publisher.